A Comparison Study of Radioactivity and Radiation Hazard Index between Legal and Illegal Cigarettes - Mohd Ariff, Muhammad Shafiq Najemee; Abdullah, Haslaile; A. Jalil, Siti Zura (International Journal of Integrated Engineering, 2018)
Radioactive nuclide which emits radiation and damages biological tissue is found in the cigarette. Illegal cigarettes are reported to contain higher toxic levels of the nuclide as compared to the legal cigarettes. Therefore, this study aims to compare the radioactive elements, concentration, radiation dose and Radiation Hazard Index (RHI) of the legal and illegal cigarettes. The natural radionuclides of Uranium-238 (238U), Thorium-232 (232Th) and Potassium-40 (40K) of six legal cigarette brands and six illegal cigarette brands were measured using a High Purity Germanium (HPGe) detector-based gamma spectroscopy system. The radioactive elements that were detected by gamma spectrometer were Lead-214 (214P) and Bismuth-214 (214Bi) from 238U decay series, Bismuth-212 (212Bi) and Actinium-228 (228Ac) from 232Th decay series and 40K. The activity and concentration of 238U for legal cigarettes were significantly higher than illegal cigarettes (p<0.01). On the contrary, a significantly high value of activity and concentration of 40K element of illegal cigarettes were recorded when compared with legal cigarettes (p<0.001). The mean value of RHI for both illegal and legal cigarette samples were calculated and found to be higher than the safe limit of unity (1). However, the statistical test to compare the RHI of internal hazard index (Hin) and external hazard index (Hex) between illegal and legal cigarettes was not significant. To conclude, both legal and illegal cigarettes were subjected to a high radiation exposure, which could have negative effects to health.